1993
DOI: 10.1002/1520-6629(199307)21:3<234::aid-jcop2290210308>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing retailer knowledge, attitudes, and behaviors related to cigarette sales to minors

Abstract: The present study employed a pre‐post, two‐group design to evaluate the effects of an educational/community‐based retailer intervention on retailer knowledge, attitudes, and behaviors related to tobacco sales to minors. In addition, the association between retailer behavior change and knowledge/attitude change was investigated. Results showed positive pre‐post changes in intervention retailers' knowledge and behavior, and moderate shifts in attitudes. However, the association between behavior change and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other authors have found that compliance with smokefree air [ 27 ] or minor’s access regulations [ 28 ] is related to awareness of regulations. In this study, awareness of the Tobacco Control Act among retailers was relatively low (43 %), but did not correspond with violations of POS provisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have found that compliance with smokefree air [ 27 ] or minor’s access regulations [ 28 ] is related to awareness of regulations. In this study, awareness of the Tobacco Control Act among retailers was relatively low (43 %), but did not correspond with violations of POS provisions.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring awareness of the Tobacco Control Act with only one item may have also been a limitation. Measuring awareness or knowledge of specific provisions as conducted in prior studies may have better correlated with compliance [ 28 ]. Additionally, there was little variance in the dichotomous measure of whether retailers had a formal source of information about tobacco control regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that counseling programs can change retailer knowledge, attitudes, and behaviors related to cigarette sales [ 9 ] and restrict tobacco sales to youths [ 10 ]. Applying the empowerment concept to assist people in developing the critical capability of self-awareness, recognizing their personal situations, and improving their problem-solving capabilities enables them to have more control over their daily lives [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the studies conclude that the best way to limit youth access to tobacco is an ongoing combination of community education, retailer and corporate education, and statewide and local enforcement. Woodruff et al found that changes in knowledge and attitudes of retailers were weakly associated with positive changes in behaviours, leading them to conclude that environmental, sociocultural, and situational factors may be necessary to change retailer behaviour 8. More recently, deterrence theory was used to design a community based intervention to increase merchant perception of risk of being detected non-compliant with youth tobacco access policies 9…”
mentioning
confidence: 99%